The Implementation of Islamic Business Ethics in Practice: The Income Smoothing Method in Islamic Banking - Wirdiansah, Muhamad; Anton Priyo Nugroho; Mawftiq, Rarasati; Muhammad Arif Yahya (Department of Islamic Banking, 2025)
Purpose:This study examines Islamic business ethics in income smoothing within Islamic banking. It analyzes whether income smoothing aligns with Islamic ethics principles of fairness, transparency, and accountability, and its implications for stakeholder trust and institutional integrity. Methodology:A qualitative approach was used, which included looking at the content of Islamic banks' financial statements and talking to important people, like Shariah board members and financial experts. The study also incorporated a review of relevant Islamic jurisprudential texts to assess compliance with Shariah principles. Findings:Although income smoothing is a common practice to stabilize profit distribution and ensure customer satisfaction, its implementation raises ethical concerns, according to the research. Some practices may inadvertently conflict with the principles of transparency and honesty in financial reporting. However, when applied within Shariah-compliant frameworks, income smoothing can enhance the stability of Islamic banks and foster stakeholder trust. Implication:The findings highlight the necessity of implementing stricter regulatory oversight and formulating comprehensive guidelines to align income-smoothing practices with Islamic business ethics. Banks should prioritize ethical considerations to maintain their Shariah-compliant status and uphold public trust. Originality:This study contributes to the limited body of research on the intersection of Islamic business ethics and income smoothing practices. It offers a novel perspective by integrating Shariah principles into the discussion of financial management strategies in Islamic banking.